The openness hypothesis in the context of economic development in Sub-Saharan Africa: The moderating role of trade dynamics on FDI - Simplice Asongu; Joseph Nnanna; Paul N. Acha-Anyi (African Governance and Development Institute (AGDI), 2020)
This study investigates the simultaneous openness hypothesis by assessing the importance of trade openness in modulating the effect of foreign direct investment (FDI) on economic dynamics of gross domestic product (GDP) growth, real GDP and GDP per capita. The focus of the study is on 25 countries in Sub-Saharan Africa over the period spanning from 1980 to 2014. First, trade imports modulate FDI to induce net positive effects on GDP growth and GDP per capita. Second, trade exports moderate FDI to generate overall positive impacts on GDP growth, real GDP and GDP per capita. Implications of the study are discussed, inter alia: (i) both FDI and trade infrastructures are necessary for FDI-focused measures to engender positive economic development outcomes in host communities and countries. (ii) Macroeconomic conditions that are relevant for promoting economic development are necessary for the interactions between trade openness and FDI to generate favorable outcomes in terms of GDP growth, real GDP and GDP per capita.
Keywords: E23; F21; F30; L96; O55; 330; Economic Output; Foreign Investment; Sub-Saharan Africa